2006
DOI: 10.1021/om0508029
|View full text |Cite
|
Sign up to set email alerts
|

Formation of PPh2C6F5 through Phosphido Platinum and/or Palladium(III) Intermediates,

Abstract: The two-electron oxidation reactions of the neutral [(C6F5)2M(μ-PR2)2M‘(NCCH3)2] (M = M‘ = Pt or Pd, M = Pt, M‘ = Pd) complexes using I2 as oxidant have been investigated by experimental (R = Ph) and electronic structure calculation methods (R = H). It was found that a reductive coupling of PR2 and C6F5 takes place along the reaction pathway for all oxidized complexes. The most salient structural features of the [(C6F5)2Pt(μ-PR2)2Pd(C6F5)2]2-, [(C6F5)2Pd(μ-PR2)2Pd(acac)]-, and [(C6F5)2Pt(μ-PR2)2PtI2] complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 58 publications
(87 reference statements)
7
74
0
Order By: Relevance
“…The Pd(III)e Pd(III) P-containing intermediates are expected to give 31 P NMR signals in a very low field (cf. data for compounds VIII, Chart 1) [25]. No signals above 130 ppm were observed in the 31 P NMR spectra of the studied reactions.…”
Section: Possible Mechanism Of the Aminophosphine Formationmentioning
confidence: 83%
“…The Pd(III)e Pd(III) P-containing intermediates are expected to give 31 P NMR signals in a very low field (cf. data for compounds VIII, Chart 1) [25]. No signals above 130 ppm were observed in the 31 P NMR spectra of the studied reactions.…”
Section: Possible Mechanism Of the Aminophosphine Formationmentioning
confidence: 83%
“…We have recently reported a straightforward method for the synthesis of the heterodinuclear complex [(C 6 F 5 ) 2 Pt(lPPh 2 ) 2 Pd(NCCH 3 ) 2 ] (3) [3], as a yellow solid and studied some reactions of this complex. We observed that CH 2 Cl 2 solutions of 3 at room temperature became dark in colour and, after work up of the mixture, a purple solid was isolated.…”
Section: Resultsmentioning
confidence: 99%
“…Complexes [(C 6 F 5 ) 2 M(lPPh 2 ) 2 M 0 (NCCH 3 ) 2 ] (M = Pt, M 0 = Pd 3; M = M 0 = Pt, 4, Pd 5) were prepared as described in the references [3,59].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, only the X-ray crystallographic data for this compound are available. The 31 P{ 1 H} NMR spectra of known di-m-PPh 2 Pd(II) complexes usually have the signals of the bridging PPh 2 group between À100 and À140 ppm [19,20,34,35,37]. We were able to isolate two complexes, 4a,c, which presumably have dimeric cyclopalladated structure with two bridging PPh 2 ligands.…”
Section: Structure Confirmationmentioning
confidence: 88%